Primary education in Morocco: Evolution and contrasts in educational reforms - AIT BEN ASSILA , Rachid (Revue Internationale du Chercheur, 2022)
In Morocco, the low level of student achievement and the growing inequalities in primary education are among the most pronounced deficits. These deficits prevent any attempt to develop an inclusive growth model (OECD, 2017). Despite the efforts made before and after the promulgation of the national education and training charter, quality still remains a value that struggles to prevail. The generalization of access, and although having substantially reduced the inequalities of access, has not been accompanied by efforts to improve the quality of learning. This article attempts to present a brief overview of the evolution of primary education in Morocco, the objective being to identify the advances and constraints that are hindering its development. Thus, in the first section we will present the main evolutionary chronicles of this teaching cycle. In the second section we will try to highlight the main contrasts and fractures in the education policies adopted by Morocco since independence. The aim is to be able to identify the gaps in relation to the objectives set both during the first years following independence and in those covered by the National Education and Training Charter.